Microscopic origin of highly enhanced current carrying capabilities of thin NdFeAs(O, F) films. Issue 8 (26th June 2019) - Kauffmann-Weiss, Sandra; Iida, Kazumasa; Tarantini, Chiara; Boll, Torben; Schneider, Reinhard; Ohmura, Taito; Matsumoto, Takuya; Hatano, Takafumi; Langer, Marco; Meyer, Sven; Jaroszynski, Jan; Gerthsen, Dagmar; et al.
Abstract : The physical properties of FBS depend strongly on crystal structure, chemical composition and microstructure. Abstract : Fe-based superconductors present a large variety of compounds whose physical properties strongly depend on the crystal structure and chemical composition. Among them, the so-called 1111 compounds show the highest critical temperature T c in the bulk form. Here we demonstrate the realization of excellent superconducting properties in NdFeAs(O1− x F x ). We systematically investigated the correlation between the microstructure at the nanoscale and superconductivity in an epitaxial 22 nm NdFeAs(O1− x F x ) thin film on a MgO single crystalline substrate ( T c = 44.7 K). Atomic resolution analysis of the microstructure by transmission electron microscopy and atom probe tomography identified several defects and other inhomogeneities at the nanoscale that can act as extrinsic pinning centers. X-Ray diffraction and transmission electron microscopy displayed a broad variation of the a -axis lattice parameter either due to a partially strained layer at the interface to the substrate, high local strain at dislocation arrays, mosaicity, or due to composition variation within the film. The electrical transport properties are substantially affected by intrinsic pinning and a matching field corresponding to the film thickness and associated with the Bean–Livingston surface barrier of the surfaces. The thin film showed a self-field critical current density J c (4.2 K) of ∼7.6 MA cm −2 and a record pinning force density of F p ≈ 1 TN m −3 near 35 T for H ‖ ab at 4.2 K. These investigations highlight the role of the microstructure in fine-tuning and possibly functionalizing the superconductivity of Fe-based superconductors.